A holistic retrofitting approach to UK residential buildings - a combined PV/PCM/Wall insulation/window system - Zhang, Yue (2025)
This study addresses the urgent need to improve energy efficiency in the construction sector, which accounts for 40% of global energy consumption. In the UK, aging residential buildings pose challenges to reducing carbon emissions, making targeted retrofit strategies essential. Current methods lack an integrated approach, so this research evaluates the combined impact of photovoltaic (PV) systems, phase change materials (PCM), insulation, and advanced glazing on energy efficiency using EnergyPlus simulations.